Alcohol detoxification completion, acceptance of referral to substance abuse treatment, and entry into substance abuse treatment among Alaska Native people. (February 2017) - Running Bear, Ursula; Beals, Janette; Novins, Douglas K.; Manson, Spero M.
Abstract: Background: Little is known about factors associated with detoxification treatment completion and the transition to substance abuse treatment following detoxification among Alaska Native people. This study examined 3 critical points on the substance abuse continuum of care (alcohol detoxification completion, acceptance of referral to substance abuse treatment, entry into substance abuse treatment following detoxification). Methods: The retrospective cohort included 383 adult Alaska Native patients admitted to a tribally owned and managed inpatient detoxification unit. Three multiple logistic regression models estimated the adjusted associations of each outcome separately with demographic/psychosocial characteristics, clinical characteristics, use related behaviors, and health care utilization. Results: Seventy-five percent completed detoxification treatment. Higher global assessment functioning scores, longer lengths of stay, and older ages of first alcohol use were associated with completing detoxification. A secondary drug diagnosis was associated with not completing detoxification. Thirty-six percent accepted a referral to substance abuse treatment following detoxification. Men, those with legal problems, and those with a longer length of stay were more likely to accept a referral to substance abuse treatment. Fifty-eight percent had a confirmed entry into a substance abuse treatment program at discharge. Length of stay was the only variable associated with substance abuse treatment entry. Conclusions: Services like motivational interviewing, counseling, development of therapeutic alliance, monetary incentives, and contingency management are effective in linking patients to services after detoxification. These should be considered, along with the factors associated with each point on the continuum of care when linking patients to follow-up services. Highlights: Higher GAF scores, longer LOS, and older ages of first alcohol use were associated with detoxification completion. A secondary drug diagnosis was associated with detoxification incompletion. Those with legal problems and LOS were more likely to accept a referral to substance abuse treatment. Women were less likely than men to accept a referral to treatment. LOS was the only variable associated with substance abuse treatment entry.